Application of Social Competence (ASCAAL) to improve student learning creativity in the online learning system (SPADA) in the Covid-19 Pandemic Era - Siahaan, Mungkap Mangapul; Purba, Rudiarman; Sianturi, Tambos August (Universitas Pendidikan Ganesha, 2021)
Social competence ensures teaching objectives in the SPADA system that knows no boundaries of space and timefor teachers and students. 54% of Indonesian teachers do not have sufficient competence to teach. It has an impact on the lackoflearning objectives that are not achieved optimally. This study aims to investigate the innovation of two groups of studentsin learning English Syntactic Structure. With purposive sampling technique, ASCAAL was measured from the results ofseveral methods in the form of a questionnaire, pretest and posttest given to 45 students. The group is the controlclass and the experimental class that study Syntactic Structure. The experimental class consisted of 25 students, andthe control class consisted of 20 students. One group teaches with SPADA, and the other teaches with social media facilitiessuch as Google Classroom and WhatsApp. The technique used to analyze the data is descriptive qualitative andquantitative analysis. The result of the research is that ASCAAL is proven to be positive in increasing students'creativity. ASCAAL also supports a positive learning management system. The features and menus on SPADA show adeveloping learning creativity system that increases student motivation and value.